On the two-stage multisplitting iteration methods for linear complementarity problems - Guo, Wenxiu; Zheng, Hua; Lu, Xiaoping; Zhang, Yongxiong (Applied mathematics and computation, 2024)
In this work, the two-stage multisplitting iteration methods based on the equivalent modulus equations are analyzed for solving linear complementarity problems. New convergence results are presented where the convergence domains of the parameter matrices are enlarged compared the existing literatures. Furthermore, the improved domains are validated by numerical examples with parallel computations using OpenACC. •Propose two convergence theorems of the two-stage multisplitting iteration methods for LCPs with new proof techniques.•The given results can improve the domain of the parameter matrices in the existing literatures.•Design an OpenACC framework where the efficiency of the proposed methods is shown to be improved with good speedups.